2020
DOI: 10.3390/atmos11111254
|View full text |Cite|
|
Sign up to set email alerts
|

A Practicable Measurement Strategy for Compliance Checking Number Concentrations of Airborne Nano- and Microscale Fibers

Abstract: Despite compelling reports on asbestos-like pathogenicity, regulatory bodies have been hesitant to implement fiber number-based exposure limits for biodurable nanoscale fibers. One reason has been the lack of a practicable strategy for assessing airborne fiber number concentrations. Here, a method is proposed, detailed and tested for compliance checking concentrations of airborne nano- and microscale fibers. It relies on Poisson statistical significance testing of the observed versus a predicted number of fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…However, the threshold diameter to distinguish between rigid and non-rigid HARNs depends also on the material, and has up to now only been verified experimentally for carbon-based nanotubes or -fibers. Broßell et al ( Broßell et al, 2020 ) and Murphy et al ( Murphy et al, 2021 ) have reported a threshold diameter for the rigidity of CNTs to be above ~30 to 40 nm, while in the German Federal Institute for Occupational Safety and Health (BAuA) measurement strategy for nanosized fibers a cut-off diameter of 20 nm is used ( Meyer-Plath et al, 2020 ). This figure is based on data on MWCNTs, but includes a safety margin of about a factor of 16 for nanofibers for which no experimental data on their toxicity or rigidity is available ( Meyer-Plath et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the threshold diameter to distinguish between rigid and non-rigid HARNs depends also on the material, and has up to now only been verified experimentally for carbon-based nanotubes or -fibers. Broßell et al ( Broßell et al, 2020 ) and Murphy et al ( Murphy et al, 2021 ) have reported a threshold diameter for the rigidity of CNTs to be above ~30 to 40 nm, while in the German Federal Institute for Occupational Safety and Health (BAuA) measurement strategy for nanosized fibers a cut-off diameter of 20 nm is used ( Meyer-Plath et al, 2020 ). This figure is based on data on MWCNTs, but includes a safety margin of about a factor of 16 for nanofibers for which no experimental data on their toxicity or rigidity is available ( Meyer-Plath et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, there is a lack of chronic in vivo toxicity studies for materials with diameters between 15 and 30 nm. [ 20 , 52 , 53 ] Therefore, the second step of the present work included an evaluation of the extent of alteration of HALLMARK pathways observed for materials with high aspect ratios but length and diameter smaller than that of Mitsui‐7 and 30 nm, respectively. In this regard, we detected that the cellular effect of the NM‐400 (NRCEW26) material resembles one of the rigid fibers, although its 11 nm diameter suggests it would behave like a tangled material.…”
Section: Discussionmentioning
confidence: 99%
“…in den vergangenen zwei Jahrzehnten wurden mit metho den der Nanotechnologie große Fortschritte bei der entwick lung neuer materialien erzielt. eine neue und vielfäl tige materialgruppe sind die auf Fulleren und Graphenstrukturen basierenden Kohlenstoffmaterialien, speziell die ein und mehrwandigen Kohlenstoff nanoröhren (Carbon Nanotubes, CNT [16,17]. ein solches Bruchverhalten entlang Faserrichtung zeigten bisher vornehmlich die kristallinen pechbasierten Carbonfasern.…”
Section: Neue Materialien -Neue Erkenntnisse In Der Risikoforschungunclassified